A Theoretical and Measurement Study of Sea Ice and Ice Shelf in Antarctica as Electrically Dense Media - Albert, M. D.; Tan, T. E.; Ewe, H. T.; Chuah, H. T. (2005)
Due to Antarctica's remoteness and harsh weather condition, remote sensing technology has been an attractive tool in equipping Antarctica scientists with the monitoring information and the understanding of ice physical changes in the Antarctican ecological system. Previous Antarctica researches on remote sensing of ice mainly utilize ice and snow scattering models based on independent scattering assumption. The needs of the consideration of coherent effects of the scatterers and the measurement of physical parameters affecting such effects are addressed in this study. Theoretical model based on radiative transfer theory with the incorporation of Dense Medium Phase and Amplitude Correction Theory (DM-PACT) [1] is developed. This concept of DM-PACT derived from antenna array theory requires an understanding of the distribution statistics of the scatterers in the homogeneous host medium. The ground truth measurement of multi-year period has been conducted at sea ice and ice shelf areas near Scott Base, Ross Island in Antarctica and a series of measurement of sea ice and snow physical parameters including distribution statistics of the air bubbles in sea ice are carried out. Theoretical study of the backscattering returns and scattering mechanisms in these electrically dense media is performed and analysis of important physical parameters affecting the radar returns is presented. Satellite measurements of the test areas from Radarsat have been acquired for the comparison of model predictions and measurement data with promising results.